Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1142/s0219581x16500198
|View full text |Cite
|
Sign up to set email alerts
|

Green Route for Silver Nanoparticles Synthesis by Raphanus Sativus Extract in a Continuous Flow Tubular Microreactor

Abstract: The present work deals with the investigation of the greener route for the production of silver nanoparticles using Raphanus sativus (R. sativus) bioextract in a continuous flow tubular microreactor. The parameters affecting the particle size and distribution were investigated. From the results obtained it can be inferred that the ascorbic acid (reducing agent) present in the R. sativus bioextract is responsible for the reduction of silver ions. At optimum condition, the particle size distribution of nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…They reported that as the diameter of the channels was altered, the morphology of synthesized nanoparticles was influenced due to changes in mass transfer. A plant extract was used as a reducing agent in the preparation of Ag nanoparticles in a tubular microreactor by Jolhe et al [50]. They concluded that the presence of ascorbic acid in the bio-extract of R. Sativus Gioria et al [48] synthesized palladium nanoparticles (PdNPs) by effective utilization of green reagents like glucose and starch.…”
Section: Inorganic Nanomaterialsmentioning
confidence: 99%
“…They reported that as the diameter of the channels was altered, the morphology of synthesized nanoparticles was influenced due to changes in mass transfer. A plant extract was used as a reducing agent in the preparation of Ag nanoparticles in a tubular microreactor by Jolhe et al [50]. They concluded that the presence of ascorbic acid in the bio-extract of R. Sativus Gioria et al [48] synthesized palladium nanoparticles (PdNPs) by effective utilization of green reagents like glucose and starch.…”
Section: Inorganic Nanomaterialsmentioning
confidence: 99%
“…At the same time, quick and low-cost synthesis is highly demanded. Minireactor technology has been in use for a long time. , The need to continuously synthesize monodisperse nanoparticles gave rise to the development of custom microfluidic devices. , Monodisperse silver nanoparticles have been rapidly synthesized in a continuous flow tubular microreactor by thermal reduction of a single-phase reactant (silver pentafluoropropionate dissolved in isoamyl ether) . Similarly, synthesis of gold nanoparticles having a narrow size distribution was carried out employing a continuous flow microreactor using separately injected chloroauric acid and ascorbic acid solutions .…”
Section: Introductionmentioning
confidence: 99%